Geometric Awakening: Bridging the Formula Gap through Real-World Applications in Eastern Cape Mathematics Classrooms - Okuhle Somacala; Shakespear Chiphambo (Journal of Honai Math, 2026)
This study investigated the impact of real-world applications on enhancing Grade 10 learners’ conceptual understanding of the total surface area of a cylinder in the Eastern Cape, South Africa. Grounded in Kolb’s experiential learning theory (1984), the research adopted a mixed-method case study approach involving thirty-nine mathematics learners. Quantitative data were collected through a pre-test and post-test to measure performance changes following a three-step intervention featuring digital simulations and hands-on model construction. Qualitative data were gathered via semi-structured interviews with nine purposively selected learners and classroom observations. Quantitative analysis using a paired-samples t-test revealed a statistically significant improvement in performance (t(38) = 6.30, p < 0.001), with a mean score increase of 35.1% and a large effect size (Cohen’s d = 1.01). Qualitative findings identified four key themes: enhanced conceptual understanding, increased motivation through contextual learning, development of transferable problem-solving skills, and the effectiveness of collaborative, visual approaches. The results suggest that bridging the gap between abstract mathematical formulas and everyday cylindrical objects reduces misconceptions and fosters learner agency. This research provides empirical evidence for the effectiveness of application-based pedagogical approaches in under-resourced South African educational settings.